The earth through time - Levin, Harold L. (Hoboken, N.J. : John Wiley & Sons, 2013)
"Revised and brought up-to-date discussions such as: Geology lives in the present and in the past; When the Mediterranean was a desert; Geologic background of Charles Darwin; and Ferdinand Hayden and the geological exploration of the American west. Revised geological time scale to conform to most recent recommendation of the International Congress on Stratigraphic Nomenclature"--Provided by publisher.
Includes index.
Keywords: Historical geology